Information Technology Governance Assessment Using The Cobit 2019 Framework and ISO/IEC 38500 at RSUD XYZ - Azzahra, Berliana; Rachman, Andi Nur; Fitriani Dewi, Euis Nur (Deparment Information System, Siliwangi University, 2024)
The advancement of Information Technology (IT) is a crucial prerequisite for bolstering the efficacy and efficiency of organizational operations, encompassing healthcare establishments like RSUD XYZ. But problems like unreliable networks, antiquated computers, and a lack of IT knowledge in human resources (HR) arise. Therefore, to guarantee efficient IT usage, a thorough IT governance assessment is required. In order to help overcome current challenges, this study intends to assess IT governance at RSUD XYZ utilizing the COBIT 2019 framework and ISO 38500 standards.Three primary processes are assessed using the Capability Maturity Model Integration (CMMI) framework: Ensured Risk Optimisation (EDM03), Managed Risk (APO12), and Human Resources (APO07). According to the evaluation results, APO07 successfully attained level 4 as intended, APO12 was at level 3 of goal 5, and the EDM03 process was at level 2 of target 4. The identified competency gaps formed the basis for the preparation of improvement recommendations. In addition, this research also proposes introducing other processes such as ITIL for IT service management and TOGAF integration to support enterprise architecture.It is anticipated that these findings would enable agencies to strengthen their IT governance capacities in order to minimize current gaps and meet more ideal goals. This study offers RSUD XYZ thorough guidelines for enhancing more effective and efficient IT governance, hence facilitating the integration of IT plans with hospital business objectives.